The relationship and development trend of corporate social responsibility (CSR) literature: Utilizing bibliographic coupling analysis and social network analysis. Issue 4 (15th October 2019) - Lin, Yu-Cheng; Padliansyah, Roni; Lin, Tzu-Chiang
Abstract : Purpose: The purpose of this paper is to provide a comprehensive view of the longitudinal status and the knowledge structure of the CSR research by identifying the major study topics, the development of CSR research, the leading authors and countries, as well as the most cited reference. Design/methodology/approach: The authors systematically reviewed 14, 490 articles in 15 journals specialized in CSR published between 2000 and 2016 with bibliographic coupling analysis and social network analysis to unveil the recent trend of CSR research. Findings: The results identified 15 research topics in CSR research. This study accordingly suggests that CSR implication is the most popular topic in the CSR research field. Particularly, the publications regarding to "CSR Implication" increased with a dramatic trend. Furthermore, the rest of the 14 topics had a stagnant trend movement. Most of the leading authors of CSR research came from English-speaking countries. CSR investigations with varied topics simultaneously attracted the attentions of researchers from developed counties. On the other hand, researchers from developing countries simply focused limited issue. Originality/value: This study proposes an automatic content analysis from scientometric perspective to reveal a comprehensive and longitudinal understanding of CSR research. Such examination on CSR studies is critical to afford researchers' urgent need to grasp current research status and potential research space.